In Situ Migration Analysis and Diffusion Coefficient Determination of Bio‐Based Plasticizer From NBR Using FTIR‐ATR and Estimation of Migrated Plasticizer Contents by TGA Analysis. Issue 1 (16th April 2019) - Shahzad, Irfan; Wittchen, Sergei; Cepus, Valentin
Abstract : The migration of plasticizer from a product can restrict the usability of the product as this process affects material properties and shorten their service life. The objective of the present study is to investigate this migration process and observe its dynamics under short‐term thermal aging. For this purpose, in situ FTIR‐ATR spectra are recorded after every hour for continuous 60 h, while the plasticized and unplasticized NBR system is mounted and heated on ATR crystal with a heating plate at 70 °C. The band ratio of the corresponding characteristic peak areas from plasticizer carbonyl (1736 cm −1 ) and reference C‐H stretching from butadiene (968 cm −1 ) is determined after every hour. TGA analysis carried out on similar NBR samples with gradually increasing plasticizer amounts helped to obtain the calibration curve which is used to determine the migrated plasticizer amount. With the obtained data, it is possible to determine the diffusion coefficient and to quantify the migrated plasticizer amount during short‐term thermal aging and thus present a universal tool for the comparison of different plasticizers with respect to their migration behavior.